Semi-empirical modeling and parameter analysis for the development of a high speed resistance-welding process. (3rd July 2018) - Lang, Haoxiang; Wang, Ying; de Silva, Clarence W.
Abstract: This paper presents procedures for parameter analysis and modeling, which are applicable in the development and quality control of a high-speed-resistance welding process. Two test beds are introduced, which are used in the experimental investigation, particularly to establish efficient methodologies for welding wire mesh. Test data are acquired under different parameter settings. A linear test bed is used to establish preliminary parameter ranges for good welding. Then, the effect of welding parameters on rotary welding is studied using the second test bed. Finally, a semi-empirical model of the welding processes, which presents the relationship between the welding parameters and the welding quality, is developed. These results may be used as the basis for setting the operating parameters and for monitoring and controlling the quality, through a weld-quality index and appropriate control schemes, in a welding process.